Review of Rabies Preventions and Control - Chernet Balcha; Nejash Abdela (International Journal of Public Health Science (IJPHS), 2017)
Rabies is an acute viral infection of the central nervous system, caused by a lyssavirus in the family Rhabdoviridae. It is zoonotic viral disease that can affect all mammals, including humans, cats, dogs, and wildlife and farm animals. The virus is present in the saliva of affected animals, and the most frequent method of transmission to humans is by bites, scratches or licks to broken skin or mucous membranes. The disease has a long incubation period (six months) and symptoms may take several weeks to appear after infection. The first clinical symptom is neuropathic pain at the site of infection or wound due to viral replication. Diagnosis can only be confirmed by laboratory tests preferably conducted post mortem on central nervous system tissue removed from cranium. This paper reviews the possible prevention and control of rabies. Essential components of rabies prevention and control include ongoing public education, responsible pet ownership, routine veterinary care and vaccination, and professional continuing education. Control strategies include quarantine, confirmation of diagnosis, determining the origin and spread of an outbreak. Since rabies is invariably fatal and deadly viral disease that can only be prevented the collaborative effort between Veterinarians and human health care professionals are needed in the prevention and control of rabies.